Gender and Management: Women's Leadership, Structural Barriers, and Social Dynamics - Rojak, Jeje Abdul; Fajar, Abbas Sofwan Matlail (Bulletin of Science, Technology and Society, 2025)
This article analyses female leadership in organisations by highlighting the structural barriers, gender stereotypes, and social dynamics that shape their career paths. Based on qualitative literature studies, this research examines works in organisational and gender sociology, social psychology, and management studies published over the past two decades. Thematic analysis was used to synthesise findings regarding unequal access to strategic positions, biased assessment processes, and the subjective experiences of female leaders in negotiating their professional identities. The results show that seemingly neutral organisational structures contain formal rules and informal practices that favour masculine leadership figures, including through recruitment, promotion, project assignment, and work arrangements that assume unlimited availability. Stereotypes about women's competence and commitment, particularly those related to motherhood and family work, result in double standards in the assessment of their leadership styles and reduce their opportunities to gain strategic support. Theoretically, this article reinforces the argument that the gender gap in leadership is the result of multiple interactions between structure, culture, and agency. Practically, these findings indicate the need for a transformation of human resource policies, work design, and evaluation practices that explicitly challenge gender bias and open space for the expression of diverse female leadership.